Threshold-based selection combining for relay networks. (May 2017) - Nagarajan, V.; Balasaraswathi, M.
Abstract: A wireless system model which typically consists of a beginning node, multiple relays, and an ending node, has been considered. The conventional selection combining schemes are not suitable for cooperative diversity systems due to its inherent detection errors. The relays forward beginning node's information through a decode and forward protocol. The detection errors can be minimized by having a threshold at the relay. The relays participate in the cooperation process only if the instantaneous signal-to-noise ratio (SNR) of the beginning node to relay node is more than a fixed threshold. We derive the end-to-end symbol error probability of this scheme for M -ary phase-shift keying using paired error method for relay networks in the presence of flat Rayleigh fading. We numerically find the optimum value of relay-threshold. Numerical results show that the relay-threshold selection combining outperforms the conventional selection combining in terms of SNR gain.